Characteristics of Anemia in Patients with Chronic Hepatitis C and Ways of Their Correction - Mukhamedjanova M. Kh. (Scholars Digest Publishing, 2023)
Objective – to characterize changes in the blood system that occur during antiviral therapy for chronic hepatitis C (HCV) and modern methods for their correction. The presented scientific review provides information about the main hematological side effects and methods for their correction in modern antiviral therapy for chronic HCV infection. Conclusion. Thus, modern highly effective antiviral therapy for chronic HCV infection can be accompanied by a wide range of hematological disorders caused by various interactions of the hepatitis C virus and antiviral drugs with the bone marrow and the immune system.
Keywords: chronic HCV infection, anemia, antiviral therapy.